Tanzimat Döneminde Kıbrıs Ticareti / Trade in Cyprus during the Tanzimat Period - Samani, Hasan (Journal of History Culture and Art Research, 2017)
Abstract This study aims to investigate commercial activity in Cyprus, an Ottoman island since 1571, during the Tanzimat reform Period. The Tanzimat period that this paper focuses is not only a period in which many new institutions were established to provide a centralized and efficient administration but also it is a period that witnessed a steady increase in trade relations with European countries. Therefore, Tanzimat as the reformation of the Ottoman administration also consisted in new establishments and regulations to organize and regulate commercial activities. The influence of the period could also be seen in Cyprus as one of the most vital ports for Eastern Mediterranean trade. In this context, this study aims to clarify the commodities in island’s trade and to investigate the countries in the region and the foreign countries as leaders in export. Local merchant that are actively engaged in Cyprus trade and the reformations to increase trade in Cyprus are the other topics of the study. The Bâb-ı Âli (Sublime Porte) documents in the Ottoman archive of Prime Minister’s Office and literature provided the basis of this study. As a conclusion it could be seen that the volume of trade in Cyprus had been increased during this period. Wine, locust bean and cotton became vital commodities in island’s export. The export of some commodity was under inspection. The merchants active in trade of the island were from non-Muslim community whereas the Muslim merchants were to provide goods for foreign and non-Muslim merchants within the island. It is seen that the establishment of a Tribunal of Commerce in Tuzla (Larnaca), the construction of highway between Nicosia and Larnaca, reopening of Nicosia fair after a hundred years, were the most important reformations to stimulate trade in Cyprus. Öz Bu çalışma, Osmanlı-Türkiye yenileşme tarihinde özgün bir yere sahip Tanzimat döneminde, 1571’den beri bir Osmanlı adası olan Kıbrıs’ta ticarî faaliyetleri konu edinmektedir.Tanzimat dönemi, sadece Osmanlı devletinin merkezi ve etkin bir idari mekanizma kurmak için bir çok yeni kurumun tesis edildiği bir dönem değil, buna paralel olarak Avrupa devletleriyle ticari ilişkilerde istikrarlı bir biçimde artış yaşandığı bir dönemdir de. Dolayısıyla bu idarî yeniden yapılanma süreci, artan ticarî faaliyetleri düzenleyip kolaylaştıracak yeni kurumlar ve mevzuatı da içermektedir. Dönemin bu dinamikleri Doğu Akdeniz ticaretinde önemli bir uğrak limanı konumunda bulunan Kıbrıs’ta da etkilerini hissettirmiştir. Bu bağlamda mevcut çalışmada Kıbrıs’ta ticarî faaliyetler çerçevesinde, ada ticaretine konu olan emtiânın neler olduğu, dışsatımda öne çıkan alıcı yabancı devletler ile bölge ülkelerinin hangileri olduğuincelenmiştir. Kıbrıs ticaretinde fââl olan yerli tüccar çalışmanın konu edindiği diğer bir başlık olmuştur. Son olarak Kıbrıs ticaretini artırmaya yönelik ıslahatlara değinilmiştir. Çalışma, Başbakanlık Osmanlı Arşivi Bâb-ı Ali Belgeleri ile genel literatürden yararlanılarak hazırlanmıştır. Sonuç olarak Kıbrısın ticaret hacmi dönem boyunca artış göstermiştir. Kıbrıs’ın dışsatımında şarap, harnup ve pamuk en önemli emtia olmuştur. Bazı emtiânın dışsatımı denetim altında tutulmuştur. Kıbrıs dış ticaretini büyük ölçüde elinde tutan tüccar gayrimüslimler olmuş, Müslüman tüccar ise ada dahilinde aktif olarak yabancı ve gayrimüslim tüccara mal tedarik eden kesimi oluşturmuştur. Tuzla (Larnaka) ’da bir ticaret mahkemesinin kurulması, Lefkoşa-Tuzla şose yolunun yapımı ve tarihi Lefkoşa Panayırı’nın yeniden açılması Kıbrıs ticaretini canlandırmak için yapılan en önemli ıslahatlar olarak tespit edilmiştir.